The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1983
DOI: 10.1093/nar/11.20.6943
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of the 5′ noncoding region and part of thegaggene of mouse mammary tumor virus; identification of the 5′ splicing site for subgenomic mRNAs

Abstract: We have determined the sequence of the first 1371 nucleotides at the 5' end of the genome of mouse mammary tumor virus using molecularly cloned proviral DNA of the GR virus strain. The most likely initiation codon used for the gag gene of mouse mammary tumor virus is the first one, located 312 nucleotides from the 5' end of the viral RNA. The 5' splicing site for the subgenomic mRNA's is located approximately 288 nucleotides downstream from the 5' end of the viral RNA. From the DNA sequence the amino acid sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 38 publications
2
22
0
Order By: Relevance
“…In keeping with this notion, we observed that mouse mammary tumor virus Gag harbors an FPVV sequence which is very similar to the FPIV late-domain motif described recently for the matrix protein of Sendai virus (61). Mouse mammary tumor virus seems particularly noteworthy in this context since it contains a PTAP but no PPXY motif, like HIV Gag (11).…”
Section: Discussionsupporting
confidence: 86%
“…In keeping with this notion, we observed that mouse mammary tumor virus Gag harbors an FPVV sequence which is very similar to the FPIV late-domain motif described recently for the matrix protein of Sendai virus (61). Mouse mammary tumor virus seems particularly noteworthy in this context since it contains a PTAP but no PPXY motif, like HIV Gag (11).…”
Section: Discussionsupporting
confidence: 86%
“…3' oligo, GCGACCCCCATGAGTATATTTC (VJ83). A primer in the 5' noncoding region at the 5' splicing site for subgenomic mRNAs (31) was designed to specifically amplify spliced OILF mRNA: 5' oligo, CAGGGAACTGCAGTCTCGCCTA. The 3' oligo VJ83 described above was used to ascertain specificity for the MMTV(SW) ORF.…”
Section: Methodsmentioning
confidence: 99%
“…Unexpectedly, sequences similar to these motifs were detected in sequences complementary to the U5 regions of several mammalian retroviruses [SRV-1 (27), SRV-2 (28), MPMV (29), MMTV (30), HIV-1 (31), SIVcpz (32), EIAV (33), BIV127 (34), SA-OMVV (35)], and these sequences were located at distances from the respective primer-binding sites similar to the distance between the 3' end of the tRNA-related region and these two motifs in the SINEs (Fig. 4b).…”
mentioning
confidence: 99%